Pengaruh Pemberian Reward dan Punishment terhadap Disiplin Kerja Karyawan PT Valve Automation Indonesia - Arfita Widi Astuti; Yayat Sujatna (ITB Ahmad Dahlan Jakarta, 2021)
The attitude of employees who are excellent and skilled in their field of the company can be created by applying rewards and punishments. The positive impact of employee discipline towards PT Valve Automation Indonesia is that the work produced can positively impact company income. The purpose of this study was to explain the effect of reward and punishment on employee work discipline, to analyze the impact of reward on employee work discipline, to analyze the impact of punishment on employee work discipline, and to analyze the effect of reward and punishment partially and simultaneously on employee work discipline at PT Valve Automation Indonesia. The research design used is descriptive, quantitative, and associative methods, namely knowing the relationship between two or more variables, variable x1 (reward) and variable x2 (punishment) with symptoms or other variables, y (employee work discipline) at PT Valve Automation Indonesia. The data analysis method used in this research is multiple linear regression and multiple correlation coefficient analysis. Based on this research, the value of multiple regression analysis is obtained y = 5.091-0.487x1 + 0.385x2, which means that there is a positive relationship between giving rewards and punishments to the work discipline of PT Valve Automation Indonesia employees. Partially, there is a significant influence between reward and punishment with a significance value of 0.023 <0.05 and 0.013 <0.05 with a strong level of relationship based on the results of the correlation coefficient of 0.630 and 0.642. Simultaneously, there is a significant influence between reward and punishment on work discipline with a significance value of 0.000 <0.05 of 69.4%, the remaining 30.6% is influenced by other factors not present in this study.